Ant Lion Optimization Algorithm for Renewable Distributed Generations - Ali, E.S.; Abd Elazim, S.M.; Abdelaziz, A.Y. (Energy (Oxford), 2016)
Renewable sources can provide a clean and smart solution to the increased demands. Thus, Photovoltaic (PV) system and Wind Turbine (WT) are considered here as sources of Distributed Generation (DG). Allocation and sizing of DG have greatly affected on the system losses. This paper aims to propose Ant Lion Optimization Algorithm (ALOA) for optimal allocation and sizing of renewable DG sources in various distribution networks. First the most candidate buses for installing DG are suggested using Loss Sensitivity Factors (LSFs). Then the proposed ALOA is employed to deduce the locations of DG and their sizing from the elected buses. The proposed algorithm is tested on 33 and 69 bus radial distribution systems. The obtained results via the proposed algorithm are compared with others to highlight its benefits in reducing total power losses and consequently maximizing the net saving. Moreover, the results are introduced to verify the superiority of the proposed algorithm to improve the voltage profiles for various loading conditions. Also, the Wilcoxon test is applied to confirm the effectiveness of the proposed algorithm. •Optimal allocations and sizing of renewable DG is proposed via ALOA.•Multi-objective function is designed to improve system performance.•ALOA is applied successfully on various distribution systems and different loadings.•The superiority of ALOA is verified compared with other recent algorithms.•Wilcoxon test is performed to ensure the effectiveness of ALOA.